التفسير المقارن لسورة آل عمران من الآية-181 إلى 200 - عمارة، هاجر (University of Eloued جامعة الوادي, 2024)
"يقوم هذا البحث بدراسة: ""التفسير الـمُقارن لسورة آل عمران من الآية- 181 إلى200-"". عالجت هذه الدراسة إشكالية أساسية وهي: ماهي المواضع التي تصلح لأن تُدرس دِراسة تفسيرية مقارنة، وما هو الراجح فيها؟. وقد انْبَـنَـى من مقدمة ومبحثين وخاتمة، خصّصت المبحث الأوّل للجزء النّظري، والذي تناولت فيه التعريف بمصطلحات عنوان البحث، والمبحث الثاني خصَّصْته للجزء التطبيقي، وفسّرت فيه المواضع المختلف في تفسيرها. وخَلُص البحث إلى مجموعة من النتائج، أهمها: أن التفسير المقارن هو: بيان معنى آية بجمع الأقوال التفسيرية المختلفة، والمقارنة والموازنة بينها بالتماس أدلتها وترجيح بعضها على بعض، وذكرت وقد بينت المواضع المختلف فيها(في الآيات المحددة) وتصلح لأن تُدْرس دراسة تفسيرية مقارنة.This research studies: "Comparative interpretation of Surah Al Imran from verse 181 to 200". This study addressed a basic problem: What are the places that are suitable for a comparative interpretive study, and what is the most likely in them? It was built on two sections and a conclusion. I devoted the first section to the theoretical part, in which I discussed the definition of the terms of the research title, and I devoted the second section to the applied part, in which I explained the places that differed in their interpretation. The research concluded with a set of results, the most important of which is: Comparative interpretation is: explaining the meaning of a verse by collecting the different interpretive sayings, comparing and balancing them by seeking their evidence and preferring some over others. I have shown the places that differed (in the specified verses) and are suitable for a comparative interpretive study
مذكرة ماستر تخصص التفسير وعلوم القرآن
Keywords: آل عمران; التفسير المقارن; القران الكريم; Al Imran; Comparative Interpretation; The Holy Quran